2014
DOI: 10.5888/pcd11.140006
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Outcomes of the New York State YMCA Diabetes Prevention Program: A Multisite Community-Based Translation, 2010–2012

Abstract: IntroductionWeight loss and physical activity achieved through the Diabetes Prevention Program (DPP) have been shown to reduce type 2 diabetes risk among individuals with prediabetes. The New York State Young Men’s Christian Association (YMCA) delivered the 16-week evidence-based model at 14 YMCAs. A mixed methods process and outcomes evaluation was conducted.MethodsMost participants were referred by clinicians and were encouraged to achieve 5% to 7% weight loss. Participants were weighed weekly; additional da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…While our study supported the use of integrated research-practice partnership processes to develop physical activity programs with broad reach and organizational adoption, it does not devalue the contributions of interventions developed through the traditional pipeline model. First, it is possible that ALED would be a better fit in organizations such as the YMCA or Parks and Recreation settings where weekly community programs align with the existing delivery structure and regular programming [41,42]. Second, evidence-based interventions provide information on evidence-based principles that can be used to adapt existing, or create new, programs [38].…”
Section: Discussionmentioning
confidence: 99%
“…While our study supported the use of integrated research-practice partnership processes to develop physical activity programs with broad reach and organizational adoption, it does not devalue the contributions of interventions developed through the traditional pipeline model. First, it is possible that ALED would be a better fit in organizations such as the YMCA or Parks and Recreation settings where weekly community programs align with the existing delivery structure and regular programming [41,42]. Second, evidence-based interventions provide information on evidence-based principles that can be used to adapt existing, or create new, programs [38].…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies used interviews, 27,43,46,[48][49][50][51]58,59 three studies used focus groups, 41,53,54 and one study used a combination of interviews and focus groups. 45 The duration of the ERS across studies varied from 8 weeks, 43 10 weeks, 48,49,51 12 weeks, 45,53,58 14 weeks, 46 16 weeks, 27 26 weeks, 54 and 16 sessions over an unspecified period.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…45 The duration of the ERS across studies varied from 8 weeks, 43 10 weeks, 48,49,51 12 weeks, 45,53,58 14 weeks, 46 16 weeks, 27 26 weeks, 54 and 16 sessions over an unspecified period. 41 The following section provides overarching themes, which represent the prominent psychosocial factors identified through qualitative studies.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…The DPP reported a 24 % decrease in the incidence of diabetes 8 years following the completion of the trial [35], and the Diabetes Prevention Study (DPS) in Finland demonstrated a 43 % reduction 4 years after its completion [36]. The lifestyle intervention model of the DPP has been translated into real-world settings through primary care clinics, cardiac rehabilitation programs, churches, YMCAs, health-care facilities, and communitybased facilities [37][38][39][40][41][42][43][44][45][46] and delivered by nurse practitioners, volunteer medical personnel, YMCA trainers, lay health educators, and community health workers [26,38,41,43,[46][47][48].…”
Section: Diabetes Preventionmentioning
confidence: 99%